An English Translation and Analysis of Haruki Murakami’s Surf City of Dreams. - Hayashi, Chelsea M. (Tufts Archival Research Center, 2017)
Published in Japan in July of 1998, 'Surf City of Dreams' is one of Haruki Murakami's many lighter pieces of work that has never seen daylight in any language but Japanese. With Murakami's ever-growing fame and intrigue, this translation offers the American reader candid new insight into who this seemingly illusive author is.